Correction of multi-collector-ICP-MS instrumental biases in high-precision uranium-thorium chronology - Mason, A; Henderson, G (2010)
We present a method for the calibration of in-house thorium isotope standards for use in U-Th chronology, along with an assessment of instrumental biases on the Nu Plasma multi-collector inductively-coupled-plasma mass spectrometer. Uranium and thorium mass fractionation is found to be very strongly coupled, with no evidence of differences in mass bias behaviour. Both Th-isotope and U-Th fractionation are most closely approximated by a linear-law fractionation model. Any deviations from linear law are at the sub-permil level. We also investigate potential biases introduced by intensity-dependant, and ion-beam-path dependant variations in ion-counter response. At count rates <∼350,000 counts per second, intensity-dependant gain variation can be accounted for entirely by dead-time, while beam-path differences can cause gain variation of up to ∼0.8% for different Th isotopes. If this beam-path bias is to be adequately corrected, ion-counter measurements of Th-isotope ratios must be made with reference to bracketing Th-isotope standards measured in the same configuration. © 2010 Elsevier B.V.